2021
DOI: 10.3389/fsufs.2020.619676
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobia as a Source of Plant Growth-Promoting Molecules: Potential Applications and Possible Operational Mechanisms

Abstract: The symbiotic interaction between rhizobia and legumes that leads to nodule formation is a complex chemical conversation involving plant release of nod-gene inducing signal molecules and bacterial secretion of lipo-chito-oligossacharide nodulation factors. During this process, the rhizobia and their legume hosts can synthesize and release various phytohormones, such as IAA, lumichrome, riboflavin, lipo-chito-oligossacharide Nod factors, rhizobitoxine, gibberellins, jasmonates, brassinosteroids, ethylene, cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 163 publications
(198 reference statements)
0
73
0
2
Order By: Relevance
“…In plants, phytoestrogens do not function as hormones, instead they have an important role as phytoalexins, small molecule compounds with antifungal, antibacterial, antiviral, and antioxidant properties that are produced in response to environmental stress and pathogenic attack [5]. Among these compounds, isoflavones play a crucial role in plant-microbe interactions, such as rhizobia-legume symbiosis and defense responses in legumes, including soybeans [42,43]. In plant defense, isoflavones act as a precursor of antibacterial and/or antiherbivore activities of phytoalexins that protect the plant from pathogen infection [44,45].…”
Section: Functionality Of Isoflavones In Plantsmentioning
confidence: 99%
“…In plants, phytoestrogens do not function as hormones, instead they have an important role as phytoalexins, small molecule compounds with antifungal, antibacterial, antiviral, and antioxidant properties that are produced in response to environmental stress and pathogenic attack [5]. Among these compounds, isoflavones play a crucial role in plant-microbe interactions, such as rhizobia-legume symbiosis and defense responses in legumes, including soybeans [42,43]. In plant defense, isoflavones act as a precursor of antibacterial and/or antiherbivore activities of phytoalexins that protect the plant from pathogen infection [44,45].…”
Section: Functionality Of Isoflavones In Plantsmentioning
confidence: 99%
“…Exudates from the roots are believed to 'prime' the soil around the roots ecosystem, such that, they would recruit favorable bacteria to the rhizosphere, resulting in higher rhizosphere respiration rates and bacterial biomass percentage compared to surface soils [186]. Microorganism may respire between 64-86% of plant rhizodeposits [173,174,187,188]. Micallef et al, [189], also reported that different accessions of Arabidopsis have unique exudate profiles, and thus, their bacterial communities in rhizosphere are diverse among these accessions [189].…”
Section: Plant Genotypementioning
confidence: 99%
“…The main distinction between legumes and non-leguminous plant is that, leguminous plant associate symbiotically with N 2 -fixing bacteria from the genus Rhizobium (Alphaproteobacteria) [187,191], whereas non-leguminous plants interact in a symbiotic way with N 2 -fixing bacteria from the genus Frankia (Actinobacteria) [188,192]. The ability to colonize the rhizosphere and interact with plants is possessed by a large number of N 2 -fixing bacteria from various bacterial phyla [193].…”
Section: Leguminous and Non-leguminous Plantmentioning
confidence: 99%
“…Rhizobia are a group of microorganisms used for the formulation of bioinoculants of legumes such as Medicago sativa (alfalfa) and Glycine max (soya) seeds 1 . The symbiotic relationship between these microorganisms and alfalfa and soya crops relies on two finely tuned metabolic pathways: nitrogen fixation and denitrification 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…S. meliloti 2011 is one of the most exploited rhizobia for the formulation of bioinoculants for alfalfa seeds 1 . Genome mining revealed that this bacterium harbors two pseudoazurin genes, one located at the pSymA megaplasmid together with the Sm NirK gene ( azu1 ), and a second ( azu2 ) at the chromosome is clustered with sulfur‐related metabolism genes 19,20 .…”
Section: Introductionmentioning
confidence: 99%